2021
DOI: 10.1038/s41467-021-23864-9
|View full text |Cite
|
Sign up to set email alerts
|

WSX1 act as a tumor suppressor in hepatocellular carcinoma by downregulating neoplastic PD-L1 expression

Abstract: WSX1, a receptor subunit for IL-27, is widely expressed in immune cells and closely involved in immune response, but its function in nonimmune cells remains unknown. Here we report that WSX1 is highly expressed in human hepatocytes but downregulated in hepatocellular carcinoma (HCC) cells. Using NRAS/AKT-derived spontaneous HCC mouse models, we reveal an IL-27–independent tumor-suppressive effect of WSX1 that largely relies on CD8+ T-cell immune surveillance via reducing neoplastic PD-L1 expression and the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…The use of BPRCX807, a highly selective CXCR4 antagonist, reduced TAM polarization and recruitment, and decreased angiogenesis, tumor metastasis, and proliferation through AKT- and ERK-signaling inhibition [ 190 ]. Recently, WSX1, a receptor subunit for IL-17, has been identified as a tumor-suppressor in hepatocytes, and was proposed as a potential target for immunotherapy [ 191 ]. In this context, osteopontin, described as a prominent mediator in the immunosuppressive and inflammatory microenvironment, has been suggested as a new immunotherapy strategy in combination with anti-PD-1/PD-L1-based therapies [ 192 ].…”
Section: Targeting Cell Death and Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of BPRCX807, a highly selective CXCR4 antagonist, reduced TAM polarization and recruitment, and decreased angiogenesis, tumor metastasis, and proliferation through AKT- and ERK-signaling inhibition [ 190 ]. Recently, WSX1, a receptor subunit for IL-17, has been identified as a tumor-suppressor in hepatocytes, and was proposed as a potential target for immunotherapy [ 191 ]. In this context, osteopontin, described as a prominent mediator in the immunosuppressive and inflammatory microenvironment, has been suggested as a new immunotherapy strategy in combination with anti-PD-1/PD-L1-based therapies [ 192 ].…”
Section: Targeting Cell Death and Tumor Microenvironmentmentioning
confidence: 99%
“…Tumor suppression by downregulating PD-L1 expression in tumor cells and decreasing PD-L1/PD-1 axis-induced T-cell exhaustion in tumor cells. [191] Antitumor immune surveillance (CSF-1R inhibitor PLX3397) Orthotopic mouse model of HCC: 40 mg/kg Suppressed infiltration of TAMs, reversed M2 polarization, and decreased PD-L1 expression in HCC. [192] Abbreviations: CCL2, chemokine (C-C motif) ligand 2; CCR2, C-C chemokine receptor type 2; CSF-1R; colony stimulating factor 1 receptor; CXCL12, C-X-C Motif Chemokine Ligand 12; CXCR4, C-X-C Motif Chemokine Receptor 4; HCC, hepatocellular carcinoma; NASH, non-alcoholic steatohepatitis; NLRP3, NLR family pyrin domain containing 3; RIPK1, receptor-interacting protein kinase 1; TAMs, tumor-associated macrophages; TME, tumor microenvironment; TNFα, tumor necrosis factor alpha.…”
Section: Targeting Cell Death and Tumor Microenvironmentmentioning
confidence: 99%
“…At the mRNA level, a high level of CMTM6 is correlated with better survival in gastric cancer, colorectal cancer [20,29], while high level of CMTM6 is correlated with worse survival in gliomas [16]. At the protein level evaluated by immunohistochemistry, highly expressed CMTM6 indicates poor prognosis in gastric cancer, HNSCC, hepatocellular carcinoma [21,[30][31][32]. In our 180-dot tissue array with gastric adenocarcinoma, we confirmed that a high protein level of CMTM6 was correlated with worse survival and the co-expression of CMTM6 enhanced the prognostic value of PD-L1 in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5/CCL5 signaling pathway plays a critical in the development of HCC in chronic liver disease both in mice and humans (66)(67)(68), as a potential treatment target for HCC. Moreover, injection of WSX1 (IL-27 receptor α) can significantly suppress the HCC growth by suppressing PD-L1 expression on tumor cells via blocking phosphoinositide 3kinase delta (PI3Kδ)/protein kinase B (AKT)/glycogen synthase kinase-3β (GSK3β) pathway to release the cytotoxic effect of CD8 + T cells (69). Combined therapy with regorafenib and anti-PD-1 increased the filtration and activation of CXCR3 + CD8 + T cells via increasing CXCL10 expression in tumors, resulting in inhibition of HCC growth (70).…”
Section: Chemokine or Cytokine-mediated Treatmentmentioning
confidence: 99%